Line Bisection Test Software to Evaluate the Visual-spatial Functions in Schizophrenic Patients - Elham Tabatabaei Kashani; Elham Foroozandeh; Ayoub Bagheri (مجله انفورماتیک سلامت و زیست پزشکی, 2020)
Introduction: One way to evaluate visual-spatial functions is to use line bisection test. With the advancement of information technology, this study attempted to design a line bisection test software and investigate its efficacy compared to the conventional paper-pencil form in schizophrenic patients. Method: The present study was a causal-comparative one and line bisection test software was designed with visual studio 2015 exactly the same as the paper-pencil form. In the first stage, 30 healthy individuals were selected by purposive method according to the inclusion criteria and each of them took 3 software tests and 3 paper-pencil tests and the mean deviations were calculated from the midpoint of the line. Then, the results of the two tests were compared. In the next stage, to test visual-spatial performance, 15 schizophrenic patients were randomly selected from hospitalized psychiatric patients and both software and paper-pencil forms of line bisection test were performed for each patient. Results: Using one-way analysis of variance, the mean deviation from the mean in healthy individuals and schizophrenic patients was evaluated and the results showed no significant difference between software and paper-pencil forms (P<0.05). Due to the high accuracy of software implementation, the errors due to randomized responses are detectable by the software. Conclusion: The results of this study indicated that line bisection test software is a good alternative to paper pencil test to evaluate the spatial-visual performance of schizophrenic patients and this software can be used to evaluate cognitive functions, especially the parietal lobe injuries of schizophrenic patients.